Prevention of Contact Dermatitis Due to Hand Hygiene in The Era of COVID-19 - Damayanti, Damayanti; Anggraeni, Sylvia; Prakoeswa, Cita Rosita Sigit; Umborowati, Menul Ayu (Faculty of Medicine, Universitas Airlangga, 2021)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus is known to cause COVID-19 (Coronavirus Disease 2019), and it is rapidly spreading throughout the world that it is declared as a global pandemic. Hand hygiene is widely promoted as it is recommended to reduce the risk of COVID-19 transmission. Contact dermatitis is one of the risks of hand hygiene campaign during the COVID-19. Purpose: This study aimed to assess the parents' level of knowledge before and after health education about contact dermatitis due to hand hygiene. Methods: This was a cross-sectional study, and the data was collected via questionnaires. This study involved 53 respondents. Result: There was a significant increase in respondents' knowledge level after being educated (Wilcoxon test, p=0.000), as evidenced in the mean score of pre-test and post-test evaluation. Conclusion: To lower the incidence, education on contact dermatitis prevention due to hand hygiene during the COVID-19 pandemic is required.